2017
DOI: 10.1002/art.40178
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Management of IgA Vasculitis (Henoch‐Schönlein) in Adults: Data From 260 Patients Included in a French Multicenter Retrospective Survey

Abstract: This series constitutes the largest series of adults with IgAV reported in the literature so far. It provides data on clinical and histologic presentation and therapeutic efficacy, suggesting that CS alone appears to be a reasonable first-line therapy in patients with IgAV, while the benefit of adding CYC to CS remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 26 publications
3
70
0
14
Order By: Relevance
“…For adult IgAV patients, the annual hospital admission rate (0.42 per 100 000) is somewhat lower than reported from Denmark (0.8 from 1977 to 1983), the UK (1.3 from 1990 to 1994) and Scotland (1.1 from 1995 to 2007) . As the overall case distribution of children versus adults (75 vs 25%), as well as age and gender characteristics were comparable with other studies in adult patients, it again raises the question whether this truly could reflect a lower disease incidence in adults in WA. Adult patients did demonstrate significantly more joint, renal and gastrointestinal findings than childhood patients, confirming other studies and forming the likely explanation for the longer LOS observed in adults .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…For adult IgAV patients, the annual hospital admission rate (0.42 per 100 000) is somewhat lower than reported from Denmark (0.8 from 1977 to 1983), the UK (1.3 from 1990 to 1994) and Scotland (1.1 from 1995 to 2007) . As the overall case distribution of children versus adults (75 vs 25%), as well as age and gender characteristics were comparable with other studies in adult patients, it again raises the question whether this truly could reflect a lower disease incidence in adults in WA. Adult patients did demonstrate significantly more joint, renal and gastrointestinal findings than childhood patients, confirming other studies and forming the likely explanation for the longer LOS observed in adults .…”
Section: Discussionmentioning
confidence: 49%
“…The incidence of childhood IgAV reported across 14 studies mostly prior to 2000 ranged from 3 to 27 per 100 000 with the variation explained by case definitions, for example age, and case finding with most studies drawing on a form of hospital databases, for example inpatient, outpatient and/or emergency department (ED) databases . Incidence rates for adult IgAV described in two studies based on hospital data range from 0.8 to 1.8 per 100 000 with case series suggesting that IgAV is a more severe disease in adults and possibly heralding underlying malignancy . Despite being considered a self‐limiting condition, disease relapses are not infrequent with up to a third of discharged IgAV patients being readmitted .…”
Section: Introductionmentioning
confidence: 99%
“…Adult onset IgAV is associated with an increased risk for developing significant renal involvement, including higher frequency of nephrotic syndrome, hypertension, an elevated serum creatinine level, and end-stage renal disease compared with the pediatric onset IgAV (12). In particular, elderly patients were associated with a low incidence of prior infection and presence of arthritis and increased incidence of hypertension and high serum IgA levels (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of severe involvement in adults IgA vasculitis remains controversial, with no evidence that combination of glucocorticoids and immunosuppressive agents improved long-term outcome. 29,30 By analogy with other severe autoimmune diseases, CYC has been used in adult patients with organ-or life-threatening manifestations in only one randomized controlled trial. Pillebout et al compared corticosteroids with or without CYC in patients with severe IgA vasculitis, mainly proliferative glomerulonephritis and/or gastrointestinal manifestations, but none of them had pulmonary involvement.…”
Section: Iga Vasculitismentioning
confidence: 99%